Childhood adversity and health: The mediating roles of emotional expression and general trust - Hirano, Hiroki; Ishii, Keiko (Frontiers in Psychology, 2024)
Abstract Introduction: This study examined whether adverse childhood experiences, positive emotional expressivity in personal (i.e., expressing positive emotions when good things happened to oneself) and social settings (i.e., expressing positive emotions when good things happened to others such as friends or family), and general trust predict levels of happiness and loneliness among American and Japanese participants. We also explored whether these two types of emotional expression and general trust mediate the relationship between adverse childhood experiences and happiness/loneliness. Method: American and Japanese participants who agreed to participate in the current study first completed the Subjective Happiness Scale. Next, they answered the Emotion Expression Questionnaire, the 5-item General Trust Scale, and the revised UCLA Loneliness Scale. They then responded to the Risky Family Questionnaire. Finally, they answered demographic questions (e.g., age, gender). We hypothesized that regardless of culture, adverse childhood experiences would be negatively (positively) associated with happiness (loneliness), while positive emotional expression in personal and social settings and general trust would be positively (negatively) related to happiness (loneliness). We also predicted that positive emotional expression in both personal and social settings, as well as general trust, would mediate the relationships between adverse childhood experiences and happiness/loneliness. Results: As expected, adverse childhood experiences were negatively (positively) associated with happiness (loneliness), while positive emotional expression in personal and social settings and general trust were positively (negatively) related to happiness (loneliness). Besides, positive emotional expression in a personal situation mediated the relationships between adverse childhood experiences and happiness/loneliness, such that greater early life adversity was negatively linked to positive emotional expressivity in a personal setting, which, in turn, predicted lower happiness and higher loneliness. Discussion: The present study advances the understanding of the psychological mechanisms linking adverse childhood experiences to happiness and loneliness by highlighting the significant role of positive emotional expression in a personal situation. This result underscores the importance of developing therapeutic practices and public health strategies that foster authentic emotional expression in response to personal achievement or fortune, regardless of cultural background.